2018
DOI: 10.1108/ara-03-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting change in developing countries: evidence from Libya

Abstract: Purpose The purpose of this paper is to investigate the change in management accounting and control systems (MACSs) within two large public manufacturing companies in Libya so-called Trucks and Buses Company (TBC) and National Trailers Company (NTC). Design/methodology/approach The paper is based on semi-structured interviews, an analysis of documents and observations. It draws on New Institutional Sociology (NIS) perspective (DiMaggio and Powell’s 1983) as theoretical framework to provide explanations regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 75 publications
3
19
0
2
Order By: Relevance
“…During recruitment, employers prefer students who have graduated from accredited institutions. Hence, conformity to coercive pressure is perceived as the key to an organization’s survival and competitiveness (Lasyoud et al , 2018). For example, by conforming, organizations may not suffer in the market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During recruitment, employers prefer students who have graduated from accredited institutions. Hence, conformity to coercive pressure is perceived as the key to an organization’s survival and competitiveness (Lasyoud et al , 2018). For example, by conforming, organizations may not suffer in the market.…”
Section: Discussionmentioning
confidence: 99%
“…An institution refers to “a set of rules that govern human behavior and shapes social relations” (Lichtenstein, 1996, p. 244). The actions of organizational actors are externally pressured and shaped by societal actions (Meyer and Rowan, 2006; Lasyoud et al , 2018). This theory is used in this study because it provides a sociology-based alternate perspective, given the strong institutional-environment pressures governing accounting education.…”
Section: An Institutional Theory Frameworkmentioning
confidence: 99%
“…Dalam konteks globalisasi dan lingkungan bisnis yang semakin kompetitif dewasa ini, merupakan tantangan bagi suatu entitas usaha untuk mempertahankan efisiensi operasinya (Lasyoud et al, 2018). Keberhasilan suatu entitas usaha tergantung pada banyak keputusan manajerial yang didasarkan pada informasi akuntansi, khususnya akuntansi manajemen (Burns and Scapens, 2000).…”
Section: Pendahuluanunclassified
“…Akuntansi manajemen adalah juga alat untuk menganalisis dan mengevaluasi realisasi pengeluaran, pendapatan dan laba (Ediraras, 2011, Maharsi, 2000, Mardikawati et al, 2014, Sigilipu, 2013. Akuntansi manajemen memainkan peranannya yang terbesar sebagai alat bagi manajemen untuk membuat keputusan, meningkatkan daya saing pada sebagian entitas bisnis (Lasyoud et al, 2018, Panjaitan et al, 2018.…”
Section: Pendahuluanunclassified
“…Carpenter and Feroz (2001) and Ezzamel et al (2007) found that state regulative factors have an impact on the formation of MCSs. Lasyoud et al (2018) found that the main factors in shaping the operations of MCSs were the need to comply with political pressures, the government’s laws and regulations and the influence of professional associations. Hoque and Hopper’s (1994) study, also, confirms the conclusions of other studies claiming that the broader social, economic, political and institutional contexts govern the ways MCSs operate in the organization.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%